Venire contra factum proprium e os recursos cíveis - Raguza, Carlos Henrique (2025)
This doctoral thesis aims to contribute to the adequate use of procedural powers. To this end, it is proposed to analyze the theory of proper acts (venire contra factum proprium), which is not a recent creation of humanity, but has regained its importance with the historical mitigation of the freedom of expression of will of the parties in favor of rescue social values such as, among many others, good faith and security in legal relationships. A society that longs for the resumption of ethical and social values, such as justice, equality and opportunity, must collaborate for the rational use of public services, cooperating so that the process serves a greater purpose that supersedes the merely subjective interests of parties. In addition to many other procedural optimization mechanisms, as occurs with the system of qualified precedents, the venire contra factum proprium performs its function in parallel, enabling the law applicator to use an important basis for not knowing resources, especially when the particular interest is opposed to the constitutional and procedural values inherent to the right of action and its extension, to each act carried out by the parties. In this way, it is proposed to address the theory of venire contra factum proprium from its historical origin, treatment in other countries and how it is used in Brazilian law, proposing a concept for it. Furthermore, it will be analyzed how the theory is applied to civil appeals and how the contradictory behavior of the parties has a strong influence on the maintenance of appeal interest and, in this aspect, as a criterion for admissibility. Finally, the purpose of this study is to contribute another element of unquestionable relevance to optimize judicial provision, in particular the usefulness of venire contra factum proprium as a criterion for weighing (subjective) appeal interest